EAHIL Council Elections 2015-2018 - candidates (Journal of EAHIL, 2017)
Candidate for Belgium - Inge DiscartCandidate for Denmark - Jette Frost JepsenCandidate for Finland - Elise JohanssonCandidate for Finland - Tiina HeinoCandidate for Italy - Valeria ScottiCandidate for Norway - Jannicke Rusnes LieCandidate for Romania - Octavia-Luciana MadgeCandidate for Slovenia - Vesna CafutaCandidates for Spain - Rebeca Isabel Gómez, Alicia F. Gómez, Virgili Páez, Veronica Juan QuillisCandidates for Sweden - Sara Janzen, Marie Folkesson Jonsson, Yvonne Hultman Özek, Helen Sjöblom, Margareta Sundin, Linda ThornCandidates for UK - Deirdre Beecher, Anne Donnelly, Isla Kuhn, Helen Buckley WoodsÂ